2018
DOI: 10.5194/hess-22-3375-2018
|View full text |Cite
|
Sign up to set email alerts
|

Dual-polarized quantitative precipitation estimation as a function of range

Abstract: Abstract. Since the advent of dual-polarization radar technology, many studies have been conducted to determine the extent to which the differential reflectivity (ZDR) and specific differential phase shift (KDP) add benefits to estimating rain rates (R) compared to reflectivity (Z) alone. It has been previously noted that this new technology provides significant improvement to rain-rate estimation, primarily for ranges within 125 km of the radar. Beyond this range, it is unclear as to whether the National Weat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In particular, a combination of Z and DR for input variables of the ML-based models leads to a good QPE performance. Studies have reported that this combination leads to the best performance among combinations of Z, DR, and KD for the ZR relationship-based model [46,47]. In many cases, application of DR, except for combinations of DR and KD, lead to a large improvement in the QPE using the ML-based model, unlike the ZR relationship-based model.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a combination of Z and DR for input variables of the ML-based models leads to a good QPE performance. Studies have reported that this combination leads to the best performance among combinations of Z, DR, and KD for the ZR relationship-based model [46,47]. In many cases, application of DR, except for combinations of DR and KD, lead to a large improvement in the QPE using the ML-based model, unlike the ZR relationship-based model.…”
Section: Discussionmentioning
confidence: 99%
“…Various precipitation estimators, most often in the form of R(Z H ), R(Z H , Z DR ), R(K DP ), and R(K DP , Z DR ), are proposed for dual-pol C-band and S-band weather radars [54][55][56]. Algorithms used for radar rainfall estimation are based on different combinations of the above-listed products.…”
Section: Dual-polarization Weather Radarsmentioning
confidence: 99%
“…Whereas traditional Z-R conversion is well documented in numerous applications of radar, there are recent advances in the application of dual-polarized radars which enable more accurate QPE assessment using polarimetric parameters (e.g. Anagnostou & Anagnostou, 2008;Anagnostou et al, 2004;Bringi & Chandrasekar, 2001;Bringi et al, 2011;Li, 2020;Mishra et al, 2016;Ochoa-Rodriguez et al, 2019;Scarchilli et al, 1993;Simpson & Fox, 2018). Polarization of a radar signal characterizes the orientation of the electric field (both transmitted and received).…”
Section: Radar Data Quality Rainfall Estimation and Radar Data Adjustmentmentioning
confidence: 99%